Activation mechanism and activity of globupain, a thermostable C11 protease from the Arctic Mid-Ocean Ridge hydrothermal system - Røyseth, Victoria; Hurysz, Brianna M.; Kaczorowska, Anna-Karina; Dorawa, Sebastian; Fedøy, Anita-Elin; Arsın, Hasan; Serafim, Mateus Sá M.; Myers, Samuel A.; Werbowy, Olesia; Kaczorowski, Tadeusz; Stokke, Runar; O’Donoghue, Anthony J.; et al. (Frontiers in Microbiology, 2023)
Deep-sea hydrothermal vent systems with prevailing extreme thermal conditions for life offer unique habitats to source heat tolerant enzymes with potential new enzymatic properties. Here, we present the novel C11 protease globupain, prospected from a metagenome-assembled genome of uncultivated Archaeoglobales sampled from the Soria Moria hydrothermal vent system located on the Arctic Mid-Ocean Ridges. By sequence comparisons against the MEROPS-MPRO database, globupain showed the highest sequence identity to C11-like proteases present in human gut and intestinal bacteria. Successful recombinant expression in Escherichia coli of the wild-type zymogen and 13 mutant substitution variants allowed assessment of residues involved in maturation and activity of the enzyme. For activation, globupain required the addition of DTT and Ca²⁺. When activated, the 52 kDa proenzyme was processed at K137 and K144 into a 12 kDa light- and 32 kDa heavy chain heterodimer. A structurally conserved H132/C185 catalytic dyad was responsible for the proteolytic activity, and the enzyme demonstrated the ability to activate in-trans. Globupain exhibited caseinolytic activity and showed a strong preference for arginine in the P1 position, with Boc-QAR-aminomethylcoumarin (AMC) as the best substrate out of a total of 17 fluorogenic AMC substrates tested. Globupain was thermostable (Tm activated enzyme = 94.51 ± 0.09℃) with optimal activity at 75 ºC and pH 7.1. By characterizing globupain, our knowledge of the catalytic properties and activation mechanisms of temperature tolerant marine C11 proteases has been expanded. The unique combination of features such as elevated thermostability, activity at relatively low pH values and ability to operate under high reducing conditions makes globupain a potential intriguing candidate for use in diverse industrial and biotechnology sectors.